Placebo effects in allergen immunotherapy: an experts’ opinion - Frew, Anthony J.; Pfaar, Oliver (Allergo journal international, 2018)
Placebo effects are common in medicine. Randomised clinical trials help us to understand their magnitude in different therapies. There are particular problems with placebo effects in allergen immunotherapy (AIT) as it is difficult to blind the active treatment and the endpoints are largely subjective. This may explain why large placebo effects are often found in AIT trials. Patients receiving open label AIT get the benefit of the active and placebo components but it can be difficult to say how much benefit is due to the active component. The use of active placebos has been proposed but brings its own problems (ethical and scientific). An EAACI Task Force has been established to address these issues. Here we review the current literature on the placebo effect in general, with a special focus on AIT trials, and indicate what we believe to be important considerations and unmet needs in AIT trial design.
Gesehen am 12.09.2019